PENGARUH PENGENDALIAN INTERNAL, WHISTLEBLOWING SYSTEM, DAN KOMITMEN ORGANISASI TERHADAP PENCEGAHAN KECURANGAN DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL MODERASI - Megawati Anggoe; Reskino Reskino (Jurnal Akuntansi Trisakti, 2023)
The aims of this research were to verify the effect of Internal control, Whistleblowing system, and organizational commitment on Fraud prevention; and to verify whether individual morality moderate the effect of Internal control, Whistleblowing system, and organizational commitment on Fraud prevention. The research method uses explanatory research, data collection techniques use primary data obtained from distributing questionnaires. The research sample consisted of 100 employees at state-owned banks consisting of Bank BNI, Bank BRI, Bank BTN, and Bank Mandiri. Data analysis techniques were carried out with the help of statistics, namely Structural Equation Modeling (SEM). The results of the study show that internal control, whistleblowing systems, organizational commitment, and individual morality have an effect on fraud prevention. Meanwhile, individual morality is able to moderate the influence between internal control, whistleblowing system, and organizational commitment to fraud prevention. Meanwhile, the magnitude of the influence of fraud prevention can be explained from the presence of internal controls, white blowing systems, and organizational commitment, as well as the moderating effect of individual morality at 81.2%.